2021
DOI: 10.3389/fcell.2021.641315
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 in Senescence and Aging-Related Cardiovascular Diseases

Abstract: SIRT6 belongs to the nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases and has established diverse roles in aging, metabolism and disease. Its function is similar to the Silent Information Regulator 2 (SIR2), which prolongs lifespan and regulates genomic stability, telomere integrity, transcription, and DNA repair. It has been demonstrated that increasing the sirtuin level through genetic manipulation extends the lifespan of yeast, nematodes and flies. Deficiency of SIRT6 induces chronic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 213 publications
(262 reference statements)
0
34
0
Order By: Relevance
“…First, we evaluated the effects of different doses of PD (20 μM, 40 μM, and 80 μM) on the autophagy flux in CP-treated HK-2 cells. WB results showed that, compared with the control, CP (20 μM) significantly induced the increase of LC3 II and p62 expression (Figures 3(a Increasing evidence shows that SIRT6-mediated autophagy has a positive effect on cell survival [31]. To confirm whether SIRT6 is involved in the cytoprotective effect of PD against CP, the CP-induced HK-2 cells were treated with PD combined with or without OSS-128167, an inhibitor of SIRT6, to evaluate the relationship between SIRT6 and autophagy flux.…”
Section: Pd Attenuated Cisplatin-induced Apoptosis Of Hk-2mentioning
confidence: 91%
See 2 more Smart Citations
“…First, we evaluated the effects of different doses of PD (20 μM, 40 μM, and 80 μM) on the autophagy flux in CP-treated HK-2 cells. WB results showed that, compared with the control, CP (20 μM) significantly induced the increase of LC3 II and p62 expression (Figures 3(a Increasing evidence shows that SIRT6-mediated autophagy has a positive effect on cell survival [31]. To confirm whether SIRT6 is involved in the cytoprotective effect of PD against CP, the CP-induced HK-2 cells were treated with PD combined with or without OSS-128167, an inhibitor of SIRT6, to evaluate the relationship between SIRT6 and autophagy flux.…”
Section: Pd Attenuated Cisplatin-induced Apoptosis Of Hk-2mentioning
confidence: 91%
“…It has been widely reported the role of energy signaling pathways mediated by mTOR, AMPK, and NAD + metabolism in the regulation of autophagy in CP nephrotoxicity [1]. Sirtuin 6 (SIRT6) belongs to NAD + -dependent deacetylase, which is widely expressed in mammalian organs, and regulates multiple biological processes, including inflammatory response, oxidative stress, telomere homeostasis, and autophagy [31]. The protective effect of SIRT6 activating autophagy has been proved in different organ injuries, including I/R injury [39][40][41], diabetes [42][43][44][45], and sepsis [19,46,47].…”
Section: ⁎⁎mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent statistical report released by the American Heart Association (AHA) and National Institutes of Health (NIH) showed that cardiovascular disease (CVD) has a higher incidence than other common diseases, even more than the combination of lung diseases and cancer ( Bozaykut et al, 2020a ; Virani et al, 2020 ; Li et al, 2021 ). Older people are prone to develop any kind of CVD (heart failure, hypertension, stroke, coronary heart disease) and aging has been proposed to be the main risk ( Rodgers et al, 2019 ).…”
Section: Cellular Senescence and Cardiovascular Agingmentioning
confidence: 99%
“…Multiple SIRT6 pathways are related to senescence, oxidative stress and inflammation. SIRT6 counters oxidative stress by inhibiting c-Jun, Notch1 and Notch4 transcription and protein kinase B (AKT) phosphorylation via metal regulatory transcription factor 1 (MTF1) and BRG1-associated factor 170 (BAF-170) recruitment, resulting in the downregulation of inflammatory cytokines expression [ 28 ]. SIRT7 regulates stem cell senescence and heterochromatin stabilization; its deficiency accelerates the aging process while its activity displays a beneficial role [ 29 ].…”
Section: Sirtuins As Modulators Of Chronic Degenerative Diseasesmentioning
confidence: 99%